Racism against Black soccer players in the English Premier League - Zinyemba, Douglas Takudzwa (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This study analyses racism against black players in the English Premier League. To that end, this thesis studies online articles published between 2018 and 2021 by two British tabloids, namely, The Daily Mail and The Sun, to make sense of the various ways in which black soccer players experience racism. This thesis uses the theoretical concept of "racial xenophobia" to analyse and understand expressions of antipathy towards black players playing in the Premier League. A key finding in the thesis suggests that fans and players racially abuse black players in the stadiums by liking them to animals and treating them as sub-human. Another finding in the study is that fans use the bad performances of black players as an excuse to racially abuse them via social media platforms. Social media in the 21st century has now accelerated the rate at which racism is perpetrated as fans now have more access to players through their accounts. The study also found that tabloids do not only report about racist abuse but are also guilty of portraying black players in racially stereotypical ways. This research concludes that racism against black players remains a constant feature of football in the English Premier League from the time black players started to feature in the sport in the 1970s.
Keywords: Racism in sports; Soccer players -- England; Athletes, Black -- England; FA Premier League; Racism in mass media; Soccer fans; Race discrimination; Online hate speech